NT-pro-BNP Level is Related to Left Ventricular Remodeling in Patients With Primary Aldosteronism - Wu, Tao; Xu, Chenxiao; Tang, Lu; Wu, Xi; Peng, Pengfei; Yue, Xun; Cheng, Wei; He, Shuai; Li, Lei; Chen, Yucheng; Ren, Yan; Sun, Jiayu (Experimental and Clinical Endocrinology & Diabetes, 2024)
Aims To assess the relationship between the left ventricular remodeling parameters of cardiac magnetic resonance and NT-pro-BNP in patients with primary aldosteronism (PA).Methods Seventy-four PA and 39 essential hypertension patients were prospectively recruited and underwent cardiac magnetic resonance. Plasma NT-pro-BNP was measured before patients underwent cardiac magnetic resonance. Left ventricular remodeling parameters were defined as left ventricular function parameters, T1 mapping parameters, and strain parameters. Differences in continuous variables between two groups were analyzed using Student’s t-test or Mann–Whitney U test. Differences in categorical variables between two groups were analyzed by chi-squared test. Spearman’s correlation and linear regression were used to analyze the relationships between left ventricular remodeling parameters and plasma NT-Pro-BNP level. P<0.05 was considered as statistically significant.Results Patients with PA demonstrated higher NT-pro-BNP [86.0 (49.5, 145.5) vs. 45.0 (28.5, 73.5) pg/mL, P=0.001] and Native T1 (1227±41 vs. 1206±43 ms, P=0.015) level than essential hypertension patients. Compared to patients with normal NT-pro-BNP levels, those with abnormal levels demonstrated different left ventricular remodeling parameters. NT-pro-BNP level was independently related to native T1 (β=0.316, P=0.006), extracellular volume (β=0.419, P<0.001), short-axis global circumferential strain (β=0.429, P<0.001), four-chamber global longitudinal strain (β=0.332, P=0.002), and four-chamber global radial strain (β=-0.334, P=0.004) in patients after adjusting for baseline characteristics.Conclusions NT-pro-BNP level was related to left ventricular remodeling parameters derived from cardiac magnetic resonance in patients with PA. This result implies that clinicians should pay attention to NT-pro-BNP assessment in patients with PA in routine clinical assessment.
Keywords: primary aldosteronism; cardiac magnetic resonance imaging; NT-pro-BNP; left ventricular remodeling